2020
DOI: 10.1183/23120541.00126-2020
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intensive care admission in children with severe acute asthma in the Netherlands: a prospective multicentre study

Abstract: RationaleSevere acute asthma (SAA) can be fatal, but is often preventable. We previously observed in a retrospective cohort study, a three-fold increase in SAA paediatric intensive care (PICU) admissions between 2003 and 2013 in the Netherlands, with a significant increase during those years of numbers of children without treatment of inhaled corticosteroids (ICS).ObjectivesTo determine whether steroid-naïve children are at higher risk of PICU admission among those hospitalised for SAA. Furthermore, we include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Children with SAA admitted to the PICU mostly have single organ failure. We showed 14 that they have a relatively short PICU stay (mean: 3.5 days), low intubation rate (16%), and low mortality (2%) compared to the general PICU population 15‐18 . Nevertheless, a PICU admission might confront children and parents with the perception that asthma, although a chronic and often mild disease, can be fatal.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Children with SAA admitted to the PICU mostly have single organ failure. We showed 14 that they have a relatively short PICU stay (mean: 3.5 days), low intubation rate (16%), and low mortality (2%) compared to the general PICU population 15‐18 . Nevertheless, a PICU admission might confront children and parents with the perception that asthma, although a chronic and often mild disease, can be fatal.…”
Section: Introductionmentioning
confidence: 85%
“…This study was the preplanned follow‐up of our nationwide multicenter prospective study, in which 221 children (aged 2‐18 years) with SAA admitted to a Dutch PICU (n = 110) or GW (n = 111) were enrolled between 2016 and 2018 14 . We prospectively identified all children (2‐18 years old) with SAA admitted to all seven Dutch academic PICUs (N = 110) and the pediatric wards of four participating general hospitals (N = 111).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Review of Asthma Deaths (NRAD) had reported that two-third of the asthma deaths could be preventable if they were attentively managed in primary care 3 . Identifying children in whom a tailored asthma management may prevent PICU admission could target those with asthma symptoms for over a week, older and/or exposed to tobacco smoke 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide the number of children and teenagers requiring paediatric intensive care unit (PICU) admission has increased significantly over the past decade. 1 In England and Wales, there are 32 specialist PICU's which provide high-acuity care for critically ill children and teenagers. 2 Teenagers have been defined as young people aged between 13 and 18 years old.…”
Section: Introductionmentioning
confidence: 99%